Enabling Things to Talk : Designing IoT Solutions with the IoT Architectural Reference Model. - Bassi, Alessandro; Bauer, Martin; Fiedler, Martin; Kramp, Thorsten; van Kranenburg, Rob.; Lange, Sebastian; Meissner, Stefan (Berlin, Heidelberg : Springer Berlin / Heidelberg, 2013)
This volume presents the results of a flagship European Commission project to map the conceptual reference model for the Internet of Things. It sets out an agreed IoT architecture of maximal interoperability, ready for use in real-world network development.
Registry Office.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books